Living with mild cognitive impairment: the patient's and carer's experience. - Dean, K; Wilcock, G (2012)
BACKGROUND: Mild cognitive impairment (MCI) is a relatively common condition and rates of diagnosis are likely to increase in the near future. Little is known about the experiences of patients with MCI and their carers nor about the most appropriate interventions to support this group. METHODS: The existing literature on this topic up to July 2011 was identified via systematic searches of the Embase and Medline databases, the Cochrane Library and relevant sections of the National Electronic Library for Health. The main search term "mild cognitive impairment" was used in combination with other relevant terms. The reference lists of reviewed articles were also examined for any additional papers of significance. Papers identified by this method were examined and those deemed relevant were included in this review. RESULTS: Twenty-one suitable papers were identified for inclusion in this review, a relatively small number. The studies reviewed suggest that patients with MCI and their carers face a variety of practical and emotional challenges. No interventional studies of support have been undertaken, but the authors of relevant observational studies have suggested provision of information, psychosocial support and strategies to enhance patient interaction with carers and social contacts. CONCLUSIONS: MCI results in significant challenges for both patients and their carers. Further work is required in order to establish the best way to help patients and carers meet these challenges.